The What, Why and How of Generic Skills: A Financial Planning Case Study - Craig Cameron; Mark Brimble; Julie Knutsen; Brett Freudenberg (Australasian Accounting, Business and Finance Journal, 2014)
Financial planning in Australia is moving away from its traditional characterisation as an “industry” and towards a “profession”. A key feature of any profession is an educational framework that facilitates the development of technical knowledge and generic skills by students so that they can successfully transition into the workplace. The Australian Securities and Investments Commission (ASIC) is currently reviewing changes to that educational framework (ASIC 2011; ASIC 2013), while the Financial Planning Association (FPA) has recently introduced revised and enhanced educational requirements through the Financial Planning Education Council (FPEC) (FPA 2010; FPEC 2012). Stakeholder input will be critical for the development of financial planning education programs that meet the higher standards of a profession. In particular, what are the generic skills needed by financial planners; and which are currently seen to be most deficient? This paper is an instrumental case study involving interviews with 24 financial planning firms which explore the what, why and how of generic skills. This qualitative study provides a greater insight into generic skills by identifying skill importance and deficiency, as well as possible solutions to assist with the financial planning industry moving to a profession.
Keywords: generic skills; financial planning; profession; graduates; educational framework